Assessment of Palatal Throat Form in Lateral Cephalogram and its Correlation with the Skeletal Base and Facial Divergence: An Institutional Based Study - Sapkota, B.; Koju, S.; Mahanta, S. K.; Rimal, U. (Kathmandu University Medical Journal, 2021)
Background Along with peripheral seal, palatal throat form also has significant value to achieve good retention and stability of maxillary complete denture. The palatal throat form also determines the posterior extention of maxillary dentures and affects the comfortability of the patients. Objective To analyse the palatal throat form in a Nepalese population based on age, gender malocclusion and facial divergence. Method This study consisted of 300 randomly selected radiographs with a mean age of 21.46±5.62 years. Skeletal malocclusion in lateral palatal throat form outlines. Patient were also categorized according to different Schudy’s facial divergence angle (SNMP). The obtained data was tabulated based on the age, gender, palatal throat form, type of malocclusion and facial divergence. The results obtained were subjected to a statistical analysis to find the relation between variants of the soft palate and types of malocclusion in different gender groups. Result Proportion between palatal throat form and malocclusion found to be significant. There is no significant difference in proportion of different class of palatal throat form between genders. Whereas Class II palatal throat form found to be most common in all facial divergence. Conclusion It was observed that Class II malocclusion was most common among three types. The relation between palatal throat form and malocclusion, was found to be statistically significant.